2005
DOI: 10.1002/chi.838
|View full text |Cite
|
Sign up to set email alerts
|

Holidays for children and families in need: an exploration of the research and policy context for social tourism in the UK

Abstract: Although provision of holidays for families in need has been mainstreamed within the social care policies of many countries in the rest of Europe, ‘social tourism’ has yet to be adopted in the United Kingdom. This article reports on a scoping study of research and policy in this area. While there is limited robust research on the impact of holidays, emerging evidence supports a range of claims for benefits to children and families. The article concludes that both political emphasis on social inclusion and pan‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 11 publications
2
41
0
2
Order By: Relevance
“…Everything was intended to enable the children to relax, have fun, make friends, develop new relationships and new skills, and experience different ways of living in an environment that was largely happy, positive and supportive. As such, the research broadly supports existing knowledge about the positive contribution that holidaying makes to well-being, relaxation, social interaction and social bonding found in the general literature (Hobson andDietrich 1994, Richards 1998) in that dealing with people experiencing disadvantage (Hughes 1991, Voysey 2000 as well as in that which deals specifically with families and youth/children in disadvantaged contexts (Lewis 2001, Hazel 2005, Corlyon and La Placa 2006.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Everything was intended to enable the children to relax, have fun, make friends, develop new relationships and new skills, and experience different ways of living in an environment that was largely happy, positive and supportive. As such, the research broadly supports existing knowledge about the positive contribution that holidaying makes to well-being, relaxation, social interaction and social bonding found in the general literature (Hobson andDietrich 1994, Richards 1998) in that dealing with people experiencing disadvantage (Hughes 1991, Voysey 2000 as well as in that which deals specifically with families and youth/children in disadvantaged contexts (Lewis 2001, Hazel 2005, Corlyon and La Placa 2006.…”
Section: Discussionsupporting
confidence: 81%
“…Some researchers have speculated that the benefits accruing to the individual and the family can contribute to financial and social benefits for society in general (Corlyon andLa Placa 2006, Hazel 2005). Hazel (2005), for example, suggested that improved access to holidays could reduce the pressure on health and social services, citing the Canadian Council on Social Development (1984) which found that holiday participation improved relationships, reduced drug abuse and mitigated against youth crime. Benefits might also reduce the societal burden of children becoming involved in drug abuse or youth crime (Stephenson 2000;ETB 1976, cited in Hazel 2005.…”
Section: Holidaying and Well-beingmentioning
confidence: 99%
See 3 more Smart Citations